2018
DOI: 10.1186/s13104-018-3736-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of angiomatoid fibrous histiocytoma after unplanned excision: a case report

Abstract: BackgroundAngiomatoid fibrous histiocytoma (AFH) is a relatively uncommon soft tissue tumor of intermediate biologic potential. It occurs in subcutaneous regions of the extremities or the trunk, usually presenting in children or young adults. This is the first reported case of subcutaneous AFH that developed in the iliac region and was treated with an unplanned resection.Case presentationAn 11-year-old girl noticed a small subcutaneous nodule in the iliac region. As the nodule was asymptomatic, it was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These cases are usually treated with surgical excision with a wide local excision. 9 , 10 However, radiation therapy is utilized in cases where marginal excision is planned depending on the surgeon’s point of view. The literature shows different recurrence and metastasis rates in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…These cases are usually treated with surgical excision with a wide local excision. 9 , 10 However, radiation therapy is utilized in cases where marginal excision is planned depending on the surgeon’s point of view. The literature shows different recurrence and metastasis rates in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this minor chance of local recurrence, all AFH are treated with wide excision. Even cases who have undergone unplanned resections or were misdiagnosed initially should undergo additional extended resections ( 24 ). Follow-ups for 19 months, 61 months, and 45 months were available for case 3, case 2, and case 1, respectively, and all were uneventful.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is often radically resected with a wide margin [5]. Sometimes, unplanned surgery is performed in subcutaneous tumors, including AFH, which may cause local recurrence or distant metastasis [6,7]. Few studies have reported on the effective treatment for metastatic or unresectable AFH.…”
Section: Introductionmentioning
confidence: 99%